The Maternal Picturesque in Mary Wollstonecraft and Elizabeth Simcoe - Miller, Eric (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2023)
Mary Wollstonecraft (1759–97) and Elizabeth Simcoe (1762–1850) composed narratives of their travels: accounts influenced by picturesque theory, especially as articulated by William Gilpin. Wollstonecraft’s Letters Written During a Short Residence in Sweden, Norway, and Denmark appeared in 1796; Simcoe, a gifted artist, kept a written and visual diary of her 1791–96 sojourn in Lower and Upper Canada, as spouse of the first Lieutenant-Governor of Upper Canada, John Graves Simcoe (1752–1806). Wollstonecraft and Simcoe took small children with them—Wollstonecraft, her daughter Frances (born May 14 1794); Simcoe, her daughter Sophia (born October 25 1789) and her son Francis (born June 6 1791). Gilpin’s aesthetic program favours the irregular, the varied, the marginal; Wollstonecraft and Simcoe, divergent in avowed political convictions, adapt Gilpin’s practice and improvise modes of a specifically maternal picturesque. Domestically, the presence of children is expected; to situate them in the wilds and on frontiers changes their role—and the role of their mothers. Wollstonecraft’s account of a visit to Sarp Falls in Norway and Simcoe’s visions of Niagara (as well as of the Don River) reveal, respectively, Wollstonecraft’s apocalyptic, and Simcoe’s gradualist, sensibility. Wollstonecraft projects the presence of her daughter into the Scandinavian landscape, drawing on Shakespeare’s fairyland to introduce preternatural dimensions into an empirical-minded narrative; Simcoe figures her son Francis as a mediator between the empire in which she believes, and Indigenous peoples whom she acknowledges as central to the defence, the consolidation, and the future of the province over which her husband presides.